2018
DOI: 10.1038/s41467-018-03987-2
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive natural killer-cell leukemia mutational landscape and drug profiling highlight JAK-STAT signaling as therapeutic target

Abstract: Aggressive natural killer-cell (NK-cell) leukemia (ANKL) is an extremely aggressive malignancy with dismal prognosis and lack of targeted therapies. Here, we elucidate the molecular pathogenesis of ANKL using a combination of genomic and drug sensitivity profiling. We study 14 ANKL patients using whole-exome sequencing (WES) and identify mutations in STAT3 (21%) and RAS-MAPK pathway genes (21%) as well as in DDX3X (29%) and epigenetic modifiers (50%). Additional alterations include JAK-STAT copy gains and tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
114
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 67 publications
11
114
0
1
Order By: Relevance
“…3b). TET2 alterations were associated with development of myeloid 38 and lymphoid 39 malignancies, and a TET2 truncating variant was observed in one ANKL case 11 . The validated loss-of-function TET2 truncating variant was associated with a particularly high mutation burden in patient #165.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3b). TET2 alterations were associated with development of myeloid 38 and lymphoid 39 malignancies, and a TET2 truncating variant was observed in one ANKL case 11 . The validated loss-of-function TET2 truncating variant was associated with a particularly high mutation burden in patient #165.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence on the genomic landscape of T-LGLL pointed to a key role of somatic mutations within JAK/STAT (mostly in STAT3 and STAT5B genes) and Ras/MAPK pathways [3][4][5][6][7][8][9][10] . In ANKL and NKTCL, JAK2 and STAT3 mutations, lesions of epigenetic modifiers and tumor suppressors were detected [11][12][13] . Only scattered data are available on the molecular features underlying CLPD-NK, mainly provided by approaches targeted to exons of specific genes, with limited discovery power.…”
Section: Introductionmentioning
confidence: 99%
“…TP53 mutation was reportedly observed in only one of 14 ANKL patients in an exome-wide sequencing study. 28 Although detection of TP53-CHIP has been reported as a risk factor for developing t-MN, [11][12][13] some TP53-carrying CHIP clones themselves are not founding leukemic clones. 11 The significance of monitoring a single specific TP53-CHIP-carrying clone and its predictive value for t-MN remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these recent observations, JAK/STAT signaling has been suggested as a potential therapeutic target in LPN; ruxolitinib has been evaluated as a single agent in a pilot, proof‐of‐concept study in relapsed/refractory (R/R) HL and PMBL; a preliminary report suggested that HL patients may derive greater benefit from this approach…”
Section: Jak2 At the Crossroad Between Myeloid And Lymphoid Disordersmentioning
confidence: 99%
“…30 Notably, activating STAT mutations could not initiate leukemic cell proliferation on their own but enhanced signaling through the cytokinecytokine receptor-JAK/STAT axis when provided with a signal from upstream 37 ; in line with this finding, mutations in this signaling pathway have been reported to co-occur, at least in some cases, suggesting that they may interact and cooperate in the oncogenic process. 36 Based on these recent observations, JAK/STAT signaling has been suggested as a potential therapeutic target in LPN [38][39][40] ; ruxolitinib has been evaluated as a single agent in a pilot, proof-of-concept study in relapsed/refractory (R/R) HL and PMBL; a preliminary report suggested that HL patients may derive greater benefit from this approach. 41 This led to a phase II study in advanced, mostly refractory, HL patients: 42 In a population that was quite difficult to address (five median prior lines of treatment), ruxolitinib showed signs of clinical activity, though they were short-lived, with a favorable safety profile, suggesting it might be combined with other therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%